Women's Empowerment in Fisheries and Aquaculture Index (WEFI): Guidance Notes (Video) - Kruijssen, Froukje; Sproule, Katie (WorldFish, 2023)
This video provides a good overview of the Women's Empowerment in Fisheries and Aquaculture Index (WEFI) methodology and tools to use to carry out the research. WEFI measures the empowerment, agency and inclusion of women in fisheries and aquaculture contexts in an effort to identify ways to overcome those obstacles and constraints. The index content and themes have been inspired by the Women's Empowerment in Agriculture Index (WEFI). It has the quantitative component (the index) and a qualitative component.